(untitled) (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present research work was undertaken with the objectives to investigate the prevalence and molecular detection of the causal agents of sub-clinical mastitis (SCM) in cows at milk shed areas in Sirajganj and Pabna districts, Bangladesh. Materials and methods: A total of 300 milk samples were randomly collected from Baghabari milk shed areas of Sirajganj and Pabna districts. The milk samples were subjected for California Mastitis Test (CMT) for identifying SCM. Total 81 positive samples were then used for the isolation and identification of associated bacteria and fungi using conventional microbiological examination and biochemical tests, followed by confirmation by polymerase chain reaction (PCR) using specific primers. Besides, universal primers were used for amplification and sequencing of PCR products where specific primers were not used. Results: The overall prevalence of SCM was 51% (n=153/300). Based on bacteriological examination and biochemical tests, several bacteria were identified in this study; the orgnaisms included Staphylococcus sp. (45.68%), Streptococcus uberis (14.81%), Escherichia coli (9.88%), Proteus sp. (19.75%), Salmonella sp. (1.23%), Acinetobacter sp. (7.41%), and fungus (1.23%). PCR technique confirmed the bacteria as Staphylococcus aureus (279-bp), Streptococcus uberis (884-bp), E. coli (16SrRNA 585-bp, stx1 606-bp, rfbO157 497-bp) and Salmonella sp. (Inv-A gene796-bp). Conclusion: This study reveals that SCM in dairy cattle is persisting in Sirajganj and Pabna districts of Bangladesh. Hygienic practices should be improved, and providing technical intereventions may reduce the rate of SCM in the study areas. http://doi.org/10.5455/javar.2017.d238